Działalność literacko-kulturowa Marii Karpińskiej-Węgrzynowskiej w kontekście ukraińskiego modernizmu - Koniewa, Jarosław (Acta Polono-Ruthenica, 2008)
The article analyzes the life and poetry of a little-known Ukrainian poet of the Polish origin Maria Karpinska-Wengrenowska (1899-1963), a member of the union of the country writers „Plough” (1922-1925). In 2007, in Kiev the book Chords o f grief of this writer was published for the first time.